980 An Audit of a Surgical Ambulatory Service [SAmS] Performance Pre And Post COVID-19 - The Impact of Senior Decision Making. (4th May 2021) - Clements, J; Olukoga, T; Clements, B
Abstract: Introduction: Surgical Ambulatory Units have emerged to refine the management of unscheduled care with the aim of reducing admissions and offering timely, accurate treatment strategies. There are 12 principles which underpin an efficient ambulatory Service, one of which is to have a 'Consultant led and delivered Service'. Consequent to the COVID Pandemic we reallocated Consultants to our Ambulatory Service and reviewed the impact of this initiative. Method: Two periods - Pre COVID 6-17/1/20 and Post COVID 27/4 -10/5/20 were compared with respect to volume, case mix, procedures performed and outcomes in terms of investigations, and completed episodes. Data was retrieved from case notes and electronic databases. Results: There were no demographic differences across the groups. The case mix and referral patterns were similar as was the volume. There were no differences in procedures or investigations ordered. In the Pre COVID group 20% of sessions were Consultant led compared with 100% in the Post COVID group. In the post COVID group 64% of cases were completed on the index attendance compared with 27% in the pre COVID group. Conclusions: A Consultant presence in SAmS enhances decision making and risk management and is critical for the efficacy of the Service with respect to patient flow and resource management.